Muscle fundamental biology and mechanisms of disease - Hill, Joseph A.; Olson, Eric N. (Academic Press, 2012)
Provides insights into the three forms of muscle - cardiac, skeletal, and smooth - from molecular anatomy, basic physiology, disease mechanisms, and targets of therapy. This book focuses primarily on the biology of the myocyte. It is suitable for students, postdoctoral fellows, course directors and other faculty.